A Conceptual Content Analysis of 75 Years of Diversity Research in Public Administration. (June 2018) - Sabharwal, Meghna; Levine, Helisse; D'Agostino, Maria
Diversity is an important facet of public administration, thus it is important to take stock and examine how the discipline has evolved in response to questions of representative democracy, social equity, and diversity. This article assesses the state-of-the-field by addressing the following question: How has research on diversity in the field of public administration progressed over time? Specifically, we seek to examine how the focus of diversity has transformed over time and the way the field has responded to half a century of legislation and policies aimed at both promoting equality and embracing difference. We utilize a conceptual content analysis approach to examine articles published on diversity in seven key public administration journals since 1940. The implications of this study are of great importance given that diversity in the workplace is a central issue for modern public management.